VCAM-1-mediated neutrophil infiltration exacerbates ambient fine particle-induced lung injury. (1st March 2019) - Cui, Anfeng; Xiang, Meng; Xu, Ming; Lu, Peng; Wang, Shun; Zou, Yajuan; Qiao, Ke; Jin, Chengyu; Li, Yijun; Lu, Meng; Chen, Alex. F.; Chen, Sifeng
Graphical abstract: Fine ambient particle matter (PM2.5), a component of air pollution, is linked to inflammatory lung injury. PM2.5-induced diffuse intra-alveolar edema in the lungs is accompanied by polymorphonuclear leukocyte (PMN) activation and infiltration, as well as endothelial cell (EC) injury and VCAM-1 expression. Activated-PMNs and injured ECs exacerbate particle-induced lung injury. Through VCAM-1 upregulation, PM2.5 increases the permeability of endothelial and epithelial monolayers in vitro, and promotes PMN adhesion, chemotaxis, and migration across the monolayer. Neutropenia or soluble VCAM-1 inhibits PM2.5-induced lung injury. VCAM-1-mediated PMN infiltration is essential for a detrimental cycle of PM2.5-induced inflammation and lung injury. Highlights: Short-term exposure to fine particulate matter (PM2.5) increases PMN/WBC ratio in human. PM2.5 is deposited in alveolar space and endothelial cells, resulting in lung injury. VCAM-1-mediated PMN infiltration was essential for a detrimental cycle of PM2.5-induced inflammation and lung injury. PM2.5 increased VCAM-1 expression and epithelial/endothelial monolayer permeability Neutropenia or soluble VCAM-1 inhibited PM2.5-induced lung injury. Abstract: Background: Fine ambient particle matter (PM2.5) induces inflammatory lung injury; however, whether intratracheal administration of PM2.5 increases pulmonary polymorphonuclear leukocyte (PMN) infiltration, the mechanism of infiltration, and if these cells exacerbate PM2.5-induced lung injury are unknown. Methods: Using 32, 704 subjects, the association between blood PMNs and ambient PM2.5 levels on the previous day was retrospectively analyzed. Neutropenia was achieved by injecting mice with PMN-specific antibodies. Inhibition of PMN infiltration was achieved by pretreating PMNs with soluble vascular cell adhesion molecule-1 (sVCAM-1). The effects of PMNs on PM2.5-induced lung injury and endothelial dysfunction were observed. Result: Short-term PM2.5 (> 75 μg/m 3 air) exposure increased the PMN/white blood cell ratio and the PMN count in human peripheral blood observed during routine examination. A significant number of PM2.5-treated PMNs was able to bind sVCAM-1. In mice, intratracheally-instilled PM2.5 deposited in the alveolar space and endothelial cells, which caused significant lung edema, morphological disorder, increased permeability of the endothelial-alveolar epithelial barrier, and PMN infiltration with increased VCAM-1 expression. Depletion of circulatory PMNs inhibited these adverse effects. Replenishment of untreated PMNs, but not those pretreated with soluble VCAM-1, restored lung injury. In vitro, PM2.5 increased VCAM-1 expression and endothelial and epithelial monolayer permeability, and promoted PMN adhesion to, chemotaxis toward, and migration across these monolayers. PMNs, but not those pretreated with soluble VCAM-1, exacerbated these effects. Conclusion: VCAM-1-mediated PMN infiltration was essential for a detrimental cycle of PM2.5-induced inflammation and lung injury. Results suggest that drugs that inhibit PMN function might prevent acute deterioration of chronic pulmonary and cardiovascular diseases triggered by PM2.5.